2020
DOI: 10.1042/bsr20200241
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cell-derived secretomes for therapeutic potential of premature infant diseases

Abstract: Preterm birth is a complex syndrome and remains a substantial public health problem globally. Its common complications include periventricular leukomalacia (PVL), bronchopulmonary dysplasia (BPD), necrotizing enterocolitis (NEC) and retinopathy of prematurity (ROP). Despite great advances in the comprehension of the pathogenesis and improvements in neonatal intensive care and associated medicine, preterm birth-related diseases remain essentially without adequate treatment and can lead to high morbidity and mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 115 publications
0
7
0
Order By: Relevance
“…Besides brain injuries, therapeutic effects of growth factors present in MSCs have also been investigated for other pathologic conditions such as cutaneous injury, whereby the use of AT-MSC secretome that contains VEGF, HGF, transforming growth factor β (TGF-β), and keratinocyte growth factor (KGF) was able to induce greater cellular proliferation, trigger cell migration, and decrease the wound size at a faster rate [91][92][93][94][95]. The positive impact of these diverse growth factors in promoting angiogenesis [96], regenerating muscle tissue [97], and reducing incidences of premature infant diseases such as periventricular leukomalacia, retinopathy of prematurity, bronchopulmonary dysplasia, and necrotizing enterocolitis [98] also has been implicated.…”
Section: Stem Cells Internationalmentioning
confidence: 99%
“…Besides brain injuries, therapeutic effects of growth factors present in MSCs have also been investigated for other pathologic conditions such as cutaneous injury, whereby the use of AT-MSC secretome that contains VEGF, HGF, transforming growth factor β (TGF-β), and keratinocyte growth factor (KGF) was able to induce greater cellular proliferation, trigger cell migration, and decrease the wound size at a faster rate [91][92][93][94][95]. The positive impact of these diverse growth factors in promoting angiogenesis [96], regenerating muscle tissue [97], and reducing incidences of premature infant diseases such as periventricular leukomalacia, retinopathy of prematurity, bronchopulmonary dysplasia, and necrotizing enterocolitis [98] also has been implicated.…”
Section: Stem Cells Internationalmentioning
confidence: 99%
“…Additionally, this study found that the conditioned medium inhibited tumor proliferation for other cancer cell types, and it included a group of secreted factors that could be responsible for this. Cell-free conditioned media derived from MSCs can be enriched in growth factors, exosomes, cytokines and chemokines [47]. Even though the results obtained in our study showed that the AMMSC-CM has a pro-tumorigenic tendency, despite this difference, few studies have investigated the anti-tumor effects of these cells in 3D culture.…”
Section: Differential Acp Sensitivity Of Tumor Spheroids Induced By Ammscconditioned Mediummentioning
confidence: 66%
“…These changes in brain tissue will disrupt the cognitive, adaptive, motor, and social functions in the infant. Unlike other brain diseases with some limited therapeutic option, there is no specific treatment for PVL except for expectant and supportive management ( 36 ). Thus, researchers have begun exploring the use of MSCs for the treatment of PVL.…”
Section: Mscs For the Treatment Of Neonatal Brain Diseasesmentioning
confidence: 99%